Integrating religiosity into fraud triangle theory: findings on Malaysian police officers - Said, Jamaliah; Alam, Md Mahmudul; Abdul Karim, Zulyanti; Johari, Razana Juhaida (Emerald Publishing Limited, 2018)
Purpose – The purpose of this paper is to conduct an empirical analysis of the factors that determine the occupational fraud behavior. Design/methodology/approach – This study utilizes primary data collected by a questionnaire-based survey on 186 police officials of Malaysia including Sabah and Sarawak. Data are analyzed using descriptive statistics, factor analysis, and cross-sectional regression. Findings – The results derived in the study showed a statistically significant positive relationship between three basic variables of the fraud theory – pressure, opportunity, and rationalization with asset misappropriation. Moreover, this study revealed that religiosity is statistically significantly and negatively correlated to asset misappropriation. Therefore, the higher religiosity of an individual correlates with the lower probability involve in asset misappropriation. Practical implications – The findings will help Anti-Corruption Commission, Enforcement Agency of Integrity Commission, Police Department, and relevant agencies from Malaysia and other countries to design policies for reducing cases of fraudulent behavior. Originality/value – This study is an original work based on the primary data collection.